2019
DOI: 10.1111/sms.13574
|View full text |Cite
|
Sign up to set email alerts
|

The effect of interval sprinting exercise on vascular function and aerobic fitness of post‐menopausal women

Abstract: Menopausal transition accelerates an age-associated decrease in vascular function and a decline in aerobic fitness. The purpose of this study was to examine the effect of 8 weeks of interval sprinting cycle ergometer exercise on arterial stiffness, basal forearm blood flow, and aerobic fitness of post-menopausal women. Sixty overweight post-menopausal women were randomized into either exercise (Ex, n = 30) or control (C, n = 30) groups. Ex participants completed 24 interval sprinting exercise (ISE) sessions ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“… Studies were conducted in women who were classified as healthy [ 10 , 46 , 47 , 49 , 52 , 54 , 65 , 69 72 , 75 , 79 , 161 ], with overweight/obesity [ 44 , 50 , 51 , 53 , 55 , 60 63 , 66 , 67 , 73 , 76 , 100 , 110 , 121 , 138 , 162 , 164 , 167 , 168 ] and/or type 2 diabetes [ 100 , 162 ]. For transparency, the same cohort of women was examined in the following pairs of references: [ 50 , 121 ] and [ 73 , 138 ].…”
Section: Cardiorespiratory Fitnessmentioning
confidence: 99%
“… Studies were conducted in women who were classified as healthy [ 10 , 46 , 47 , 49 , 52 , 54 , 65 , 69 72 , 75 , 79 , 161 ], with overweight/obesity [ 44 , 50 , 51 , 53 , 55 , 60 63 , 66 , 67 , 73 , 76 , 100 , 110 , 121 , 138 , 162 , 164 , 167 , 168 ] and/or type 2 diabetes [ 100 , 162 ]. For transparency, the same cohort of women was examined in the following pairs of references: [ 50 , 121 ] and [ 73 , 138 ].…”
Section: Cardiorespiratory Fitnessmentioning
confidence: 99%
“…The effects were in the same range as those for combined exercise. Ho et al [ 44 ] demonstrated the efficiency of interval sprints in reducing arterial stiffness measured by baPWV and augmentation index (AIx) in overweight postmenopausal women. However, low-intensity resistance exercise did not alter arterial stiffness in obese postmenopausal women [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…This lack of clarity in defining exercise intensity may, in part, be responsible for the disparate findings in regard to physiological variables assessed in the studies. When high‐intensity aerobic exercise (Hoier et al, 2021 ) or sprint interval exercise (Ho et al, 2020 ) was used in an exercise intervention, cardiorespiratory fitness improved (Ho et al, 2020 ; Hoier et al, 2021 ; Swift et al, 2014 ). In contrast, exercise at low, moderate, and vigorous intensity improved arterial stiffness in postmenopausal females, suggesting exercise intensity may not be a critical factor (Ho et al, 2020 ; Sugawara et al, 2004 ; Sugawara et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…When high‐intensity aerobic exercise (Hoier et al, 2021 ) or sprint interval exercise (Ho et al, 2020 ) was used in an exercise intervention, cardiorespiratory fitness improved (Ho et al, 2020 ; Hoier et al, 2021 ; Swift et al, 2014 ). In contrast, exercise at low, moderate, and vigorous intensity improved arterial stiffness in postmenopausal females, suggesting exercise intensity may not be a critical factor (Ho et al, 2020 ; Sugawara et al, 2004 ; Sugawara et al, 2006 ). However, improvements in endothelial function have appeared less responsive to exercise interventions at any exercise intensity in postmenopausal females (Ho et al, 2020 ; Hoier et al, 2021 ), unless pre‐training endothelial function was impaired (Swift et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation